The effects of moderate exercise on measures of postprandial lipemia - Cox-York, Kimberly Ann, author; Horton, Tracy J., advisor; Pagliassotti, Michael, advisor (Colorado State University. Libraries, 2009)
Background. Elevated triglycerides (TG) and small lipid particle size are risk factors for cardiovascular disease (CVD), which are typically assessed after an overnight fast. Most individuals spend the day in the postprandial (PP) state, however, which might be more reflective of CVD risk. A single exercise bout has been shown to decrease PP TGs in response to a single, high-fat meal. The current study assessed the effect of a single bout of morning exercise on PP lipids over an entire day with 3 mixed meals of a typical macronutrient composition (34% fat, 15% protein, 51% CHO). Methods. 26 normal weight (NW) subjects and 18 subjects with metabolic syndrome (MetS) were studied. After an overnight fast, subjects exercised (treadmill walking, 60%VO2peak) or rested for 60 min then consumed breakfast, lunch, and dinner, contributing 25%, 35% and 40% of daily energy intake respectively. Fasting blood samples were collected before exercise or rest and continued throughout the day and were analyzed for PP lipids, glucose and insulin. A subset of the plasma samples were separated into triglyceride-rich lipoprotein (TRL) subfractions in which TG and cholesterol were measured. Apolipoprotein (apo) B-100 and B-48 proteins were measured in the medium-sized subfraction (TRL2) to assess particle origin, size and composition. Postprandial responses were analyzed via ANOVA (SPSS 16.0). Results. Overall, exercise had no effect on PPTG. With exercise, total apoB IAUC decreased 20% in the whole group, and total cholesterol IAUC decreased 30% in the NW group. MetS subjects maintained significantly higher TG than NW subjects over the day (p<0.001). PPTG in MetS women declined mid-day, and remained low for the rest of the study day. In MetS men, however, PPTG rose consistently from breakfast, and then leveled out post-lunch and remained high. TRL particle size (TG:apoB ratio) was 30% lower in MetS women than MetS men. TRL2 apoB-100 and B-48 were twice as high in MetS as in NW subjects, resulting in significantly smaller particles in the MetS group (p=0.01). Conclusions. Although exercise did not have a significant effect on PPTG, there were other potentially cardio-protective effects on apoB and cholesterol levels.
Keywords: apolipoprotein B; cardiovascular disease; physical exercise; postprandial lipemia; triglycerides; nutrition; kinesiology; physiology